2021
DOI: 10.1093/ibd/izab239
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Trap Density Increases With Increasing Histopathological Severity of Crohn’s Disease

Abstract: Background Intestinal neutrophil recruitment is a characteristic feature of the earliest stages of inflammatory bowel disease (IBD). Neutrophil elastase (NE) and myeloperoxidase (MPO) mediate the formation of neutrophil extracellular traps (NETs); NETs produce the bactericidal oxidant hypochlorous acid (HOCl), causing host tissue damage when unregulated. The project aim was to investigate the relationship between NET formation and clinical IBD in humans. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…With downregulation of the CD98 gene, gut homeostasis was maintained, and the susceptibility of mice to DSS-induced colitis was decreased; both would be beneficial to inflammation resolution. Myeloperoxidase (MPO), whose activity could reflect the degree of neutrophil infiltration at inflammatory sites, could be used for evaluating the severity of UC . After DSS induction, MPO activity was increased, while CNZM, CPZM, and CCZM treatment decreased the MPO activity, in which CCZM treatment exerted the best effect (Figure F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With downregulation of the CD98 gene, gut homeostasis was maintained, and the susceptibility of mice to DSS-induced colitis was decreased; both would be beneficial to inflammation resolution. Myeloperoxidase (MPO), whose activity could reflect the degree of neutrophil infiltration at inflammatory sites, could be used for evaluating the severity of UC . After DSS induction, MPO activity was increased, while CNZM, CPZM, and CCZM treatment decreased the MPO activity, in which CCZM treatment exerted the best effect (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…Myeloperoxidase (MPO), whose activity could reflect the degree of neutrophil infiltration at inflammatory sites, could be used for evaluating the severity of UC. 44 After DSS induction, MPO activity was increased, while CNZM, CPZM, and CCZM treatment decreased the MPO activity, in which CCZM treatment exerted the best effect (Figure 7F). This result demonstrated that after treatment, the neutrophil infiltration was decreased, and the severity of UC was mitigated.…”
Section: Cell Internalization Of Biomimetic Mofsmentioning
confidence: 92%
“…Extensive studies have confirmed that uncontrolled and excessive NETs are involved in the pathogenesis of autoimmune disease ( 10 , 11 ), cardiovascular disease ( 12 ), inflammatory disease ( 13 ) and cancer ( 14 ). It is worth mentioning that the function of NETs in tumors is gradually expanding.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NETs could promote gastric cancer cell proliferation, invasion, migration and epithelial–mesenchymal transition dependent on TGF-β signaling [ 23 ]. Furthermore, it has been proved that TNF-α up-regulated neutrophil elastase in vascular smooth muscle cells (VSMCs), which promoted VSMC migration, proliferation and inflammation [ 24 ] and mediates the formation of NETs [ 25 ]. VSMC proliferation is one of the key vascular pathological changes occurring during the development of hypertension [ 26 ].…”
Section: Introductionmentioning
confidence: 99%